On Traumatically Skewed Intersubjectivity. Issue 4 (19th May 2017) - Schechter, Daniel S.
ABSTRACT: Beginning with his Interpersonal World of the Infant (1985), Daniel Stern suggested that the infant is driven from birth to connect intersubjectively with his caregivers. By the final three months of the first year of life, as the infant begins to use protodeclarative pointing and jointly attends to the outer world, he also begins to jointly attend with his caregiver to their respective intrapsychic worlds, the mental states of his caregiver and himself. Clinically, analysts observe at this crucial point of development of secondary intersubjectivity mothers who, more often than not, respond only selectively and often unpredictably to their infants. In many instances, this may be motivated out of a mother's own need for regulation of emotion and arousal as we have shown in our empirical research. This article elaborates on clinical observations that, for the infant or young child to feel his traumatized mother's affective presence, he must try to enter mother's state of mind, while simultaneously, mother is seeking to self-regulate in the wake or the revival of trauma-associated memory traces, this at the expense of mutual regulation of emotion and arousal. We call this phenomenon traumatically skewed intersubjectivity . We find that children coconstruct with their traumatized mothers a new, shared traumatic experience by virtue of the toddler's efforts to share an intersubjective experience with a mother who is acting in response to posttraumatic reexperiencing. The problem is that the infant or young child has no point of reference to decipher the traumatized mother's social communication. And so, what is enacted leads to a new, shared traumatic event. Both the child's anxiety and aggression can, in this setting, easily become dysregulated, further triggering mother's anxiety and avoidance, leading thus to a vicious cycle that contributes to intergenerational transmission of trauma. Clinical examples and implications for psychoanalytically-oriented parent-infant psychotherapy will be discussed.